Study on irradiated D-mannose isolated from cranberry - Guzik Grzegorz P.; Stachowicz Wacław; Michalik Jacek (Nukleonika, 2019)
The stable EPR signal produced by ionizing radiation in crystalline D-mannose (C6H12O6) and separated from cranberries (Vaccinium oxycoccus) was studied. The isothermal heating of irradiated sample at 95°C for 10 minutes (melting point of D-mannose is 132°C) resulted in the modification and simplification of the EPR signal involved. The isotropic quartet has been recognized in the EPR signal of heat-treated sample. Molecular structure of the isotropic quartet identified in the complex EPR signal of D-mannose crystallite is proposed.